Zynga’s FarmVille, social games, and the ethics of big data mining - Willson, Michele; Leaver, Tama (Taylor & Francis, 2015)
The increasing necessity of engaging in social interaction through online commercial providers such as Facebook, alongside the ability of providers to extract, aggregate, analyse, and commercialise the data and metadata such activities produce, have attracted considerable attention amongst the media and academic commentators alike. While much of the attention has been focused on the data mining of social networking services such as Facebook, it is equally important to recognise the widespread adoption of large-scale data mining practices in a number of realms, including social games such as the well-known FarmVille and its sequels, created by Zynga. The implicit contract that the public who use these services necessarily engage in requires them to trade information about their friends, their likes, their desires, and their consumption habits in return for their participation in the service. This paper will critically explore the realm of social games utilising Zynga as a central example, with a view to examine the practices, politics, and ethics of data mining and the inherent social media contradiction. In determining whether this contradiction is accidental or purposeful, this paper will ask, in effect, whether Zynga and other big data miners behind social games are entrepreneurial heroes, more sinister FarmVillains, or whether it is possible at all to draw a line between the two? In doing so, Zynga’s data mining approach and philosophy provide an important indicator about the broader integration of data analytics into a range of everyday activities.